The spatial agglomeration of the labor manufacturing industry in Central Java Province, 2005–2015 - Muhammad Izzudin; Su Ritohardoyo; Lutfi Muta’ali (Universitas Negeri Malang, 2022)
The number of industries in Central Java is expanding, resulting in an improvement in the area’s economy. The study's objectives are as follows: (1) to examine the dynamics of manufacturing labor; (2) to examine the spatial concentration of manufacturing industry activity; and (3) to analyze variables impacting industrial sector employment. Between 2005 and 2015, this quantitative study analyzed secondary data. The descriptive analysis, time series analysis, klassen typology analysis, industry index analysis, and multiple linear regression techniques were employed to accomplish the research objectives. The study's findings are as follows: (1) the number of industries has decreased, particularly since 2007, from 6.9 percent in 2007 to 4.8 percent in 2015; (2) the spatial concentration of the manufacturing industry in Central Java is concentrated in 11 regions: Sukoharjo, Karanganyar, Kudus, Semarang, Semarang City, Purbalingga, Salatiga, Tegal, Temanggung, Pekalongan, and Pekalongan City; and (3) wage is the most important factor in the absorption of industrial labor in Central Java Province. The findings of this study also contribute to the development of economic Geography learning materials by focusing on the growth of an area driven by the manufacturing industry.